The Maritime Cultural Ecology of the Biak People: A Historical Study of the Sowek Region, Supiori Regency, Papua - Susilowati, Endang; Rinardi, Haryono; Rumbekwan, Albert; Ali, Ismail; Amaruli, Rabith Jihan (Department of History, Faculty of Humanities, Diponegoro University, 2024)
This article, using historical and ethnographic methods, explores the maritime cultural ecology of the Biak people in Sowek Village, Supiori Regency, Papua, Indonesia. Historically part of the Biak-Numfor and Supiori islands, Supiori became a separate district in 2003 under Law No. 35 of 2003. The Biak people in Sowek Village, who identify as the Sowek people, have lived in the Aruri Archipelago of Supiori Island for centuries. While their language and culture are part of the Biak-Numfor cultural family, their identity is rooted in their specific geographic location. Supiori Regency is predominantly oceanic and covered by mangrove forests, with only 25% of its land being dry. This landscape has shaped the Sowek people's reliance on marine resources and maritime trade. Contact with the outside world began long ago, facilitated by maritime trade and headhunting expeditions to Maluku, Ternate-Tidore, and the Raja Ampat Archipelago. The Sowek people navigate these waters using traditional boats such as the Wairon, Waimansusu, and Karures, guided by advanced astronomical knowledge of constellations like Orion (sawakoi) and Scorpion (romanggwandi). The maritime cultural ecology of the Biak people in Sowek Village, still preserved as a historical heritage, includes traditional fishing with nets, the cultivation of mangosteen (aibon), blacksmithing (kamasan), and the ecological conservation of mangrove forests, which serve as both fish habitats and natural fortifications for the village.